2013
DOI: 10.1271/bbb.120692
|View full text |Cite
|
Sign up to set email alerts
|

Kuromoji (Lindera umbellata) Essential Oil Inhibits LPS-Induced Inflammation in RAW 264.7 Cells

Abstract: Kuromoji (Lindera umbellata) essential oil (KEO) has long been used in Japan as a traditional medicine. It contains linalool (C 10 H 18 O), a naturally occurring small terpenoid. For this study, we investigated the antiinflammatory effect of KEO in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Mouse macrophage-like RAW 264.7 cells were stimulated with LPS. Then they were treated with 25 or 50 g/mL of KEO for 24 h. KEO suppressed LPS-induced pro-inflammatory cytokine production such as that of nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…Previously, linalool has been reported to inhibit VEGF and TGF-β1 expression in different experimental models. [35][36][37] Linalool possessed the strongest inhibitory activity against various carcinoma cells. 18,38 Apoptosis is a controlled mechanism which limits the survival of cells with irreparable cellular damage and avoids malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, linalool has been reported to inhibit VEGF and TGF-β1 expression in different experimental models. [35][36][37] Linalool possessed the strongest inhibitory activity against various carcinoma cells. 18,38 Apoptosis is a controlled mechanism which limits the survival of cells with irreparable cellular damage and avoids malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil suppressed LPS-induced pro-inflammatory cytokine production such as that of NO, IL-6, and TNF-α in a dosedependent manner. In addition, iNOS and cyclooxygenase-2 mRNA expression and protein levels were suppressed by treatment with KEO cells [19]. Cannabidiol (CBD) was isolated from flax fabric extract.…”
Section: Boswellia Ovalifoliolatamentioning
confidence: 99%
“…Histopathological analysis demonstrated that both of hydroalcoholic extract and its ethyl acetate fraction had comparable antiarthritic activity with methotrexates [39]. The 19-nor-clerodane trans-crotonin (CTN) (19) and the triterpene acetyl aleuritolic acid (AAA) (20) isolated from the stem bark of Croton cajucara Benth. Compound showed exhibited significant inhibition in the dextran-induced edema 90 minutes after the stimulus: 31.9% for CTN and 28.5% for AAA.…”
Section: Fig 2: Structures Of Compounds Having Anti-inflammatory Potmentioning
confidence: 99%
“…Flavonoids have also reportedly been isolated from several Lindera plants including Lindera umbellata, Lindera lucida, Lindera erythrocarpa, Lindera aggregata, and Lindera obtusiloba [7,8]. Lindera plants and isolated compounds have been studied for different biological activities including cytotoxic [9,10], anti-inflammatory [11,12], anti-hypertensive [13], hepatoprotective [14], and antioxidant activities [15,16].…”
Section: Introductionmentioning
confidence: 99%